2016
DOI: 10.1103/physrevb.93.195151
|View full text |Cite
|
Sign up to set email alerts
|

Electrically controlled mutual interactions of flying waveguide dipolaritons

Abstract: We show that with a system of electrically-gated wide quantum wells embedded inside a simple dielectric waveguide structure, it is possible to excite, control, and observe waveguided exciton polaritons that carry an electric dipole moment. We demonstrate that the energy of the propagating dipolariton can be easily tuned using local electrical gates, that their excitation and extraction can be easily done using simple evaporated metal gratings, and that the dipolar interactions between polaritons and between po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 36 publications
2
59
0
1
Order By: Relevance
“…2(b) as a function of electric field. The former depends on exciton Bohr radius [19] while the latter is enhanced with the increase of the effective dipole length shown in [13].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…2(b) as a function of electric field. The former depends on exciton Bohr radius [19] while the latter is enhanced with the increase of the effective dipole length shown in [13].…”
mentioning
confidence: 97%
“…Under this scheme, the coupled DX and IX share the strong oscillator strength of the direct component and the strong dipole moment of the indirect one, favoring higher polariton-polariton interactions. More recently [13], by integrating wide QWs in a simple waveguide, the formation of dipolar polaritons was observed resulting in higher interactions and therefore increased energy blueshifts when electric bias was applied. However, in both implementations only low density linear regimes are considered without examining the consequences of such enhancements on nonlinearities and polariton condensation regime.…”
mentioning
confidence: 99%
“…Here the conductive ITO strip also forms a transparent top electrode through which voltage can be applied across the sample. In Fig.3(e) we plot three 16,20 PL measurements measured when exciting at a distance of 187Âľm from the grating-coupler while applying different values of voltage across the sample with respect to the n + doped substrate. The effect of the Stark red-shift, induced by the electric field, on the dispersion can be clearly seen.…”
Section: An Electrically-active Striploaded Polariton Waveguidementioning
confidence: 99%
“…After the first experimental observation of dipolaritons [24], it was demonstrated that they have distinct response to electric and magnetic fields [29] and stronger interparticle interaction as compared to conventional polaritons [30]. Moreover, they can be used for enhanced electrical control [31,32], facilitate indirect exciton condensate preparation [33], single photon emission [34], and other optoelectronic applications. Particularly, it was predicted that dipolaritons can serve as an efficient ter-ahertz emission source [35][36][37].…”
Section: Introductionmentioning
confidence: 99%